Data Governance and Public Information Systems of Local Governments: A Post-Electronic Government System Perspective Study - Polyando, Petrus (Universitas Sultan Ageng Tirtayasa, 2025)
This study explores the implications of implementing an electronic-based government system for data governance and regional public information systems. The main objective is to show that data governance and regional public information systems after the implementation of an electronic-based government system can productively support various regional government functions. The study places changes in national policies and changes in social interactions due to information and communication technology, changing the way regional government works, where data and information are the basis for local strategic policies. The conceptual framework empirically tests policy, management, technology, and environmental factors. Informant data was analyzed, then improvements to local public data and information management were formulated. The study findings show that it has not been implemented systematically in the regions. For this reason, adequate facilities and supporting capacity are needed. Originality offers the development of system innovation and new work mechanisms in the region through the provision of technological infrastructure and system security; structuring a trusted and accountable work system; provision of competent organizers; e-government regulation; increasing public literacy and participation; and renewing government and community relations. This idea supports the concept of modern government, which prioritizes the role of ICT in various individual and social activities.